PENGARUH RASIO KEUANGAN TERHADAP PERINGKAT OBLIGASI PERUSAHAAN PERBANKAN UMUM DI BEI - Livia, Felice; Lukman, Hendro; Simina, Juni (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
Each study aims to decide the effect of Cash Adequacy Ratio, Non-Performing Loan, Loan to Deposit Ratio, and growth on bond ratings in general banking companies listed on the Indonesia Stock Exchange in 2016-2020 period. Purposive sampling method and valid data obtained as many as 20 companies for sample selection. Logistic regression analysis with SPSS version 21 program and Windows released in 2020 is the data processing technique chosen in this study. The results of this study indicate that the Cash Adequacy Ratio and Loan to Deposit Ratio has significant effect, while Non-Performing Loans and growth have no effect on corporate bond ratings. The implication of this research are the need for processing the company's Cash Adequacy Ratio and Loan to Deposit Ratio properly to be able to increase its bond rating.